THE ROLE OF CREATIVITY IN ENGINEERING - SALIHI, ATEEQU MUSTAPHA (IJRDO -Journal of Computer Science Engineering, 2016)
Creativity in engineering education is an ongoing critical issue for universities, in the sense that it helps meet the expectations for professional engineers, as well as complete the intellectual development of individuals. However, the importance of implementing creativity education in engineering education in the classroom has not been fully recognized. In this paper recent publications were reviewed in this regard, attempting to dissect what creativity means to engineers, and how they can overcome the stumbling blocks to creativity. Having explored the creative process, we suggested an operable tool based on Treffinger’s creative learning model that can be implemented in a classroom setting to facilitate creativity.